Komposisi Makanan Ikan Baronang (Siganus guttatus) pada Ekosistem Lamun di Perairan Kota Tanjungpinang - Uli Rohana Malau; Aditya Hikmat Nugraha; Ahmad Zahid (Jurnal Kelautan Tropis, 2023)
The survival of fish in the waters is strongly influenced by the availability of food. The purpose of this study was to analyze the types of food for baronang fish and determine the selectivity of food for baronang fish in seagrass ecosystems in Tanjungpinang waters. This research was conducted in May 2023 at three stations, namely Sekatap Waters (ST I), Madong Waters (ST II), and Sebauk Waters (ST III). The research data collection method was carried out by purposive sampling. Fish samples were obtained from catches using 2-inch gill nets. Epiphyte sampling on seagrass leaves was carried out randomly. The total number of fish obtained at station I was 8 fish, 10 fish for station II, and 7 fish for station III. The catches at each station were dissected and collected from their digestive tract and then preserved for analysis in the laboratory. Analysis of the data used is the index of propenderance and electivity index. The results obtained in this study were the type of food for baronang fish (S. gutttatus) found in Tanjungpinang waters consisting of groups of microalgae from the class Bacillariophyceae (Flagilaria, Coscinodiscus, Diatoma, Nitzschia, Gyrosigma, Melosira, Rhizosolenia, and Rhabdonema), Euglenophyceae (Trachelomonas), Dinophyceae (Alexandrium), Chlorophyceae (Closteriopsis), Cyanophyceae (Oscilatoria and Audouinella), Crysophyceae (Vaucheria), Rhodophyceae (Polisiphonia and Bostrychia), group of nematodes from class Secernentea (Hirschmanniella) and Adenophorea (Anaplectus), group of crustaceans from class Branchiopoda (Diaphanosoma), shrimp leg pieces (unidentified), and detritus group. Baronang fish choosing food in their surroundings.